Formation of students’ research interest through action learning - Adilzhan, Kamila; Bekalay, Nuripa; Makpal, Khamitova; Gulmira, Tashkeyeva; Zhanar, Kobenkulova (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the idea of Action Learning as a teaching method based on doing. Where there is action, there is interest. This approach to the development of individuals does not focus on what people need to learn, but on solutions to real problems. Thus, "Action Learning" means learning from action or concrete experience, as well as taking action as a result of this learning. The study began by exploring university students’ and teachers’ perceptions of student interest in science in order to design an instructional strategy for stimulating student interest in learning and pursuing science. The study is experimental in nature and shows cross-sectional results in control and experimental groups of action learning, which allows us to prove the effectiveness of the theoretical assumptions made in the literature review. Data for this study included responses from 114 students to an online science survey and interviews with eight science teachers. Therefore, in the given work, effective methods were used and compared with a traditional method, that is, students were divided into several groups. Studies were conducted using traditional methods for control groups and effective action learning methods for experimental groups; consequently, the comparative results of control and experimental groups showed significant indicators.